Penegakan Hukum Telematika terhadap Perundungan Siber di Media Sosial: Studi pada Platform Instagram - Anisa Hesti Fitriyani; Silvia Arleinia; Avisa Fitrianingrum; Graceya Iranita Tarigan (Jurnal Hukum Statuta, 2022)
This study discusses telematics law enforcement in cyberbullying cases on social media, especially on the Instagram platform. The social media Instagram was chosen because of the rampant bullying that occurred due to the high level of Instagram users and Internet penetration in the community. Then the main issues discussed in this scientific paper are the legal protection of telematics for Instagram social media users and how telematics law enforcement is for victims of cyberbullying or cyberbullying on Instagram social media. The aim is to find out the mechanism of the legal protection of telematics, especially on Instagram social media, and to find out how the tool of law enforcement against victims of bullying is by the existing telematics law. The research method used in this work is a normative research method with a statutory approach. Based on the research results conducted, both protection and law enforcement against social media users, especially for victims of bullying on the Instagram platform. It can be based on Law Number 19 of 2016 concerning amendments to Law Number 11 of 2008 regarding Information and Electronic Transactions (UU ITE), the Criminal Code (KUHP), and other international legal instruments related to the topic. In addition, legal protection on social media can also be based on community provisions or community guidelines that have been made by the platform developer, in this case, Instagram.